Accurate Simulation of the Star Point Behavior of Inverter-fed Synchronous Motors using the measured Common Mode Impedance - Fritsch, Christoph; Hahn, Ingo (ECCE Europe 2024 - Energy Conversion Congress and Expo Europe, Proceedings, 2024)
Many insulation faults in industrial applications are caused by a too high voltage to ground at the star point of the motor. This applies especially for synchronous torque motors. The reason is a rather undamped resonance frequency of the star point voltage to ground which is mitigated by the inverter common mode voltages. The worst case leading to most of the failures is at standstill where all inverter phases produce the identical output voltage. It is useful to be able to simulate this star point voltage for this use case. If the star point of the motor is accessible the voltage transfer function can be measured to be able to simulate the behavior. But in almost any case the star point is not accessible. This paper shows how to determine the star point behavior by using only the measured frequency-dependent common mode impedance and how to simulate the behavior using a simple model.
CRIS-Team Scopus Importer:2025-02-04
Keywords: insulation; partial discharge; star point voltage; synchronous motor; Three-phase motor drive